Implementasi Teknologi Peningkatan Produktivitas Lahan Kering Di Bawah Tegakan Kelapa di Maluku Utara [Implementation Technology to Productivity Increase at Dryland under Coconut in North Maluku] - Hidayat, Yayat; Lala, Fredy; Suwitono, Bayu; Aji, Himawan B; B, Bram (Pusat Penelitian dan Pengembangan Perkebunan, 2020)
Coconut land in North Maluku is potential to implement polyculture farming. Corn and soybeans are food commodities that can be used as intercrops among coconut stands to increase farmers' income. The purpose of this study was to determine the feasibility of land productivity and farming of polycarbonate systems under coconut stands as well as farmers' preferences for cultivation technology innovation. The research was carried out from May to October 2018 on coconut land owned by farmers in Bumirestu Village, East Halmahera Regency, North Maluku. The study applied integrated crop management (PTT) of corn and soybeans under coconut stands using VUB and fertilizer treatment. The analysis was used to answer the objectives, namely the calculation of land equality ratio (LER), RC ratio, and farmers' perceptions. The results showed that coconut-corn intercropping increased 92% of the efficiency of land productivity with a value of LER 1.92. Intercropping of soybeans increases 76% of land productivity efficiency with a LER value of 1.76. The increase in profits of coconut farming from the intercropping pattern of coconut - corn is Rp. 7,495,800/harvest with R/C 1.89 while from the intercropping pattern of coconut - soybean is Rp. 4,402,000/harvest with an R/C value of 1.55. Farmers' perceptions of technological innovations overlapping corn-coconut and coconut-soybean showed a positive perception. Farmers assume that technological innovations in intercropping corn-soybeans under coconut stands are beneficial, in accordance with the values and needs of the community, have low complexity, are easy to implement, and the results are significant.ABSTRAKLahan kering kelapa di Maluku Utara berpotensi untuk penerapan usahatani polikultur. Jagung dan kedelai merupakan komoditas pangan yang bisa dimanfaatkan sebagai tanaman sela di antara tegakan kelapa untuk meningkatkan pendapatan petani. Tujuan penelitian adalah untuk mengetahui kelayakan produktivitas lahan dan usahatani sistem polikutur di bawah tegakan kelapa serta preferensi petani terhadap inovasi teknologi. Penelitian dilaksanakan dari bulan Mei-Oktober Tahun 2018 di lahan kelapa milik petani di Desa Bumirestu, Kabupaten Halmahera Timur, Maluku Utara. Penelitian menerapkan pengelolaan tanaman terpadu (PTT) jagung dan kedelai di bawah tegakan kelapa dengan menggunakan varietas unggul baru (VUB) dan perlakuan pupuk. Analisis yang digunakan untuk menjawab tujuan yaitu perhitungan nisbah kesetaraan lahan (NKL), RC ratio, dan persepsi petani. Hasil penelitian menunjukkan tumpang sari kelapa-jagung meningkatkan 92% efisiensi produktivitas lahan dengan nilai NKL 1,92. Tumpang sari kelapa-kedelai meningkatkan 76% efisiensi produktivitas lahan dengan nilai NKL 1,76. Peningkatan keuntungan usahatani kelapa dari pola tumpang sari kelapa – jagung sebesar Rp. 7.495.800/panen dengan R/C 1,89 sedangkan dari pola tumpang sari kelapa – kedelai sebesar Rp. 4.402.000/panen dengan nilai R/C 1,55. Persepsi petani terhadap inovasi teknologi tumpang sari jagung-kelapa dan kedelai-kelapa menunjukkan persepsi yang positif. Petani mengganggap bahwa inovasi teknologi tumpang sari jagung-kedelai di bawah tegakan kelapa menguntungkan, sesuai dengan nilai dan kebutuhan masyarakat, memiliki kerumitan yang rendah, mudah diterapkan, dan hasilnya signifikan